Institutional factors that contribute to educational quality at a private higher education institution in Malaysia / Thian Lok Boon - Thian, Lok Boon (2014)

(untitled)
Diverse educational quality in private higher education, especially for-profit private higher education, is a prolonged issue in developing countries including Malaysia. Various quality assurance mechanisms have been enforced on private higher education institutions in Malaysia since the 1990s. Lately, certain for-profit institutions manage to evolve and establish good quality reputation while the others are still being perceived as demand-absorbing. Aiming to contribute to the knowledge in addressing the diverse educational quality issue at private higher education sector, the study focused on understanding the conception of a private higher education institution on educational quality, its experience in terms of the processes involved in the quest for educational quality and the key challenges faced, in order to identify the key institutional contributing factors. The study employed a strategic management conceptual framework since the quest for educational quality can be a form of strategic management. The study was an exploratory qualitative case study using holistic single case embedded design. The case was a purposefully sampled exemplary for-profit private university in Malaysia, supported by two exemplary faculties for collection of detailed implementation data. One-year field work was conducted to collect data from multiple sources, using observation, document analysis and semi-structured interview with the university leaders, faculty leaders and academics. The data were analysed using NVivo version 10 software. Data from multiple sources were triangulated to identify the themes to answer the research questions. The findings of the study show that for-profit private higher education institution does face multiple challenges in the quest for educational quality, especially in terms of balancing quality and profitability to ensure business sustainability. Fulfilling the business objective and ensuring educational quality are equally important in a for-profit vi institution, especially given the financial constraint and intensified competition. The findings suggest that educational quality and business motive not only can co-exist but also can synergise if properly integrated. The synergy may ensure long-term quality and profitability of private higher education. The integration of educational quality and business motive requires more relevant models for (a) conception of quality, and (b) strategic management of quality for private higher education institution. The models have emerged from the findings and answered the research questions. The core themes of the strategic management model for quality at private higher education institution include: (a) compelling purpose, mission and values, (b) value-for-money strategies that properly integrate the educational quality and for-profit motive, (c) leaders with academic and business capabilities, and intention to add value, (d) dynamic culture and progressive system, and (e) aligned community with the heart, mind and behaviour for quality. The insights of the study contribute to the existing literature in the areas of quality, quality assurance and strategic management of educational quality in private higher education. The findings also contribute to the development of government policies that may address the diverse quality issue in private higher education, to support national development. Finally, the findings contribute to sharing of good practices in the quest for educational quality among private higher education institutions in Malaysia and other developing countries experiencing similar issues.